2014
DOI: 10.3126/kumj.v11i1.11030
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Isolates and its Antibiotic Susceptibility Pattern in NICU

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

30
43
4
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(82 citation statements)
references
References 16 publications
30
43
4
3
Order By: Relevance
“…This was in accordance with the study by Shrestha, which showed that vancomycin was effective in 100 % isolates 7 . However, in study conducted by Kayagne vancomycin was effective against 14 % strains only while study by Shahian showed that ceftazidime was effective only in 22% 15,9 .…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…This was in accordance with the study by Shrestha, which showed that vancomycin was effective in 100 % isolates 7 . However, in study conducted by Kayagne vancomycin was effective against 14 % strains only while study by Shahian showed that ceftazidime was effective only in 22% 15,9 .…”
Section: Resultssupporting
confidence: 93%
“…These results were comparable with study done by Shrestha 7 . In some other studies done by Shahian 9 and Dias 14 , results showed that strains were sensitive to gentamycin only in 50 % and 63 % cultures respectively 9,14 .…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations